The Appraisals Used by Indonesian and Filipino Teachers in Casual Conversation - Sari, Rachel Kartika; Mujianto, Januarius; I. R. Agustien, Helena (English Education Journal, 2021)
The Appraisal system is a comprehensive framework that prominently accommodates word classification. These words reflect the feelings and attitudes of the speakers that might implicitly be influenced by culture and norms. To find out the differences and similarities, transcribed conversations of Indonesian and Filipino teachers in Maria Regina School were analyzed. A qualitative method is applied to interpret the findings. The manifestation of attitude, judgment, and graduation are classified accordingly based on Martin and White (2005). The finding of this research is then supported and related to the values and culture that ground the way teachers express appraisal in conversation. The result indicates that teachers are dominant in the engagement system, especially entertain items. These items reflect kinship and open discussion among teachers through questions and the use of modals. In the attitude systems, Filipino teachers are more dominant in positive security that reflect confidence and togetherness while positive happiness items are found in Indonesian teachers where they express their fascination and contentment. Indonesian teachers tend to express judgment of normality while Judgement of capability was expressed more by Filipino teachers. In the graduation system, teachers mostly use force intensification to express the degree of intensity, repetition, and quality. The significance of the research is, the readers will learn to be more considerate in expressing their feeling and emotion in casual talk, especially with people who have different backgrounds of culture.